PUBLIC RELATIONS MANAGEMENT IN OPTIMIZING SOCIAL MEDIA AS A BRANDING MEANS IN MADRASAH ALIYAH NEGERI (MAN) BONDOWOSO - Nuril Qomariyah (Jurnal Intelek Insan Cendikia, 2025)
Strengthening relations between educational institutions and the community continues to develop by utilizing online media as a means of communication and education. The use of social media as a means of branding in educational institutions is also increasingly being carried out more intensively by several educational institutions, one of which is MAN Bondowoso. The aim of this research is to determine public relations management (PR) strategies in optimizing the use of social media as a means of madrasah branding at MAN Bondowoso. This research uses field research methods with a qualitative type of research. Data collection is carried out using interview, observation and documentation techniques. As well as data analysis techniques used through three procedures, including data condensation, data presentation, and drawing conclusions. The data that has been obtained is checked for validity using triangulation techniques. The findings from this research show that MAN Bondowoso has utilized social media as a means of branding in addition to generally being a medium for information, communication, education and preachtion. There are four social media managed and developed at MAN Bondowoso, including Instagram, Facebook, YouTube and Website. The development of social media management at MAN Bondowoso in recent years has increased, due to the existence of a public relations management strategy in the management process, starting from the planning, organizing, implementing and monitoring stages.